The Internalizing Principles of Religious Moderation in Creating a Moderate Islamic Generation - Syarifah, Sabilatus; Hidayat, Fahri (Pascasarjana IAIN Metro, 2024)
This research aims to examine the role of internalizing the values of religious moderation in forming generation Z who practice wasathiyah Islam in understanding and implementing their religion. The research method is literaturestudy, a research technique that focuses on collecting data through analysis of literature from various sources relevant to the research topic. Research findings show that religious education that encourages the internalization of the values of religious moderation has a significant impact in forming generation Z who tends to instill wasathiyah Islam. Generation Z who are involved in religious education tend to have a tolerant and inclusive attitude in religious practices, and are able to carry out religious demands in a balanced manner with the values ofmoderation. Overall, religious education that prioritizes the internalization of the principles of religious moderation plays a key role in forming generation Z who understands and practices wasathiyah Islam, which in the end cancontribute to the creation of a more harmonious and inclusive society in a comprehensive context .